RAHN DALAM PEMBIAYAAN SYARIAH: ANALISIS PERBANDINGAN RAHN TASJILY DAN RAHN HIYAZI - Sa'idatun Nadiva; Anna Zakiyah Hastriana (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2026)
The uncertainty of economic fluctuations often drives individuals to optimize assets through pawning mechanisms as a tactical solution to liquidity pressures. Given that rahn implementation is divided into tasjily and hiyazi schemes, each with its own distinctive characteristics, a comparative analysis of the two is crucial to deepen theoretical and practical understanding. This study employed a library research method with a qualitative-descriptive approach that synthesized various legal literature and relevant secondary data. The results indicate that tasjily rahn emphasizes the transfer of legal documentation while retaining physical control of the asset to the debtor, while hiyazi rahn requires full physical retention of the asset by the creditor. This fundamental difference has implications for the risk profile and flexibility of asset utilization, with each model having its own distinct legal basis and operational mechanisms within the Islamic banking system. This occurs because the two instruments are constructed to accommodate different liquidity needs, with rahn tasjily more aligned with productive financing, while rahn hiyazi is more effective for short-term consumer financing with higher collateral security. This study concludes that the integration of these two standardized rahn models is crucial for strengthening the capital structure and public trust in Islamic financial institutions in Indonesia.